The Public's Preferences for Psychological Interventions During the COVID-19 Pandemic: A Discrete Choice Experiment - Li, Hui-qin; Liu, Shu-xiang; Xue, Hui; Yuan, Hua; Zhang, Xiu-ying (Frontiers in Psychiatry, 2022)
Aims: To explore the public's preference for psychological interventions through a discrete choice experiment and to provide references for formulating psychological intervention policies and establishing psychological intervention procedures in response to public health emergencies. Methods: This study is a discrete choice experiment. Attributes and levels were identified through literature reviews, in-depth interviews, focus group discussions, and expert consultations. Experimental design principles were applied to generate choice sets containing different attribute levels and develop a survey instrument. Convenience sampling was conducted nationwide, and 1,045 participants were investigated. A mixed logit model was used to evaluate the public’s preferences. Results: All attributes in our study were found to have a significant influence on the public's preferences for psychological interventions during the COVID-19 pandemic. The public’s preferences for providers and duration were influenced by the public’s levels of education and classifications. Furthermore, the most ideal scenario was found to be a one-on-one psychological intervention provided by family and friends through social network platforms, for which the frequency is twice per week, and the duration of each intervention is 0.5-1 hour. Conclusions: The public's preferences for psychological interventions during the COVID-19 pandemic are affected by the method, form, frequency, provider, and duration of interventions. Our findings provide references for the formulation of psychological intervention policies and for the establishment of psychological intervention procedures in response to public health emergencies.